General practitioners' views on leadership roles and challenges in primary health care: a qualitative study. (2nd January 2017) - Spehar, Ivan; Sjøvik, Hege; Karevold, Knut Ivar; Rosvold, Elin Olaug; Frich, Jan C.
Abstract: Objective: To explore general practitioners' (GPs) views on leadership roles and leadership challenges in general practice and primary health care. Design: We conducted focus groups (FGs) with 17 GPs. Setting: Norwegian primary health care. Subjects: 17 GPs who attended a 5 d course on leadership in primary health care. Results: Our study suggests that the GPs experience a need for more preparation and formal training for the leadership role, and that they experienced tensions between the clinical and leadership role. GPs recognized the need to take on leadership roles in primary care, but their lack of leadership training and credentials, and the way in which their practices were organized and financed were barriers towards their involvement. Conclusions: GPs experience tensions between the clinical and leadership role and note a lack of leadership training and awareness. There is a need for a more structured educational and career path for GPs, in which doctors are offered training and preparation in advance. KEY POINTS: Little is known about doctors' experiences and views about leadership in general practice and primary health care. Our study suggests that: There is a lack of preparation and formal training for the leadership role. GPs experience tensions between the clinical and leadership role. GPs recognize leadership challenges at a system level and that doctors should take on leadership roles in primary health care.